Penerapan Lafaz Haqiqah dan Majaz dalam Penetapan Hukum Keluarga Kontemporer - Yulizain Putra; Muchlis Bahar; Firdaus (As-Sakinah : Jurnal Hukum Keluarga Islam, 2026)
In the linguistic hierarchy scheme, Haqiqah occupies a superior position compared to Majaz, because Haqiqah is the main core while Majaz is only a derivative. Consequently, Majaz should not be used as the foundation for establishing Islamic law unless Haqiqah is difficult to implement, and at that time a supporting indicator (qarinah) is needed to clearly guide it. In Arabic linguistics, the term "an-nikâh" encompasses both the essential and the figurative meanings. Imam Nawawi explained that linguistically, "nikâh" means union. Sometimes, this term refers to the "marriage contract," and other times to the "husband-wife relationship." This research is qualitative through a literature study approach, relying on secondary data from relevant OJS-based books and scientific journals. From an in-depth analysis, the author concludes that the understanding of the concept of marriage in Islam—specifically the term "nikah"—can be explained through the lens of Haqiqah and Majaz. Experts in ushul fiqh and Arabic linguists state that the essence of "nikah" is "watha" (intimate relations). However, the fuqaha from the four schools of thought agree that the true essence is "agreement", while the majaz refers to "watha".